Smart Reading: Pelatihan Bedah Jurnal Sistem Informasi Berbasis Speed Reading pada Mahasiswa S1 Institut Bakti Nusantara - Winia Waziana; Dita Novita Sari; Erliza Septia Nagara (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
Academic literacy demands require undergraduate students to efficiently digest scientific articles. However, many Information Systems students at Institut Bakti Nusantara experience literacy fatigue and spend 2–3 hours understanding a single journal due to rigid, word-by-word reading methods and difficulty decoding technical components like system architectures and algorithms. This community service (PkM) implements the "Smart Reading" method through Speed Reading-based journal dissection training. The method utilizes a structured cyclic approach: laying the foundation, planning, information gathering and analysis, and acting on findings. Evaluation is conducted via direct observation of structural journal analysis worksheets and performance presentations. The training results demonstrate a significant transformation in students' critical reading habits, with the average comprehension and extraction score reaching 82%, successfully surpassing the initial target threshold of 75%. Mechanically, eliminating sub-vocalization and expanding peripheral vision accelerated the literature review synthesis process. The institutional sustainability plan involves integrating this method into student study groups to continuously foster a critical digital literacy ecosystem.